BIOMASS AND CARBON ALLOCATION IN DIFFERENT COMPONENTS OF ULMUS WALLICHIANA (ELM): AN ENDANGERED TREE SPECIES OF KASHMIR VALLEY - NASIR RASHID WANI; KHWAJA NAVED QAISAR; PARVEZ AHMAD KHAN (International Journal of Pharma and Bio Sciences, 2014)
Trees have assumed special importance after it was realized that trees could help reduce the emission of atmospheric carbon by trapping it in various pools of carbon viz. above ground biomass, below ground biomass, soil, litter and dead wood. Carbon sequestration through biomass seems to be a cheap and viable option to mitigate the increasing concentrations of greenhouse gases. The study attempted to estimate biomass and carbon allocation of 19 year old Ulmus wallichiana plantation under different diameter classes. The DBH of trees in the stand varied from 15.42 cm to 35.87 cm, height from 12.16 m to 24.47 m, basal area between 0.019 m2 to 0.101 m2 and volume between 0.101 m3 to 0.944 m3 during 2009 and 2010.The average dry stem biomass of the trees at the site varied between 61.14 kg to 566.82 kg, branch dry biomass between 19.10 kg to 179.82 kg, leaf dry biomass between 3.81 kg to 41.33 kg, total above ground dry biomass between 84.05 kg to 787.97 kg, root dry biomass varied from 21.01kg to 196.99 kg and total biomass (above + below ground) varied from 105.06 kg to 984.96 kg.The stem carbon varied from 26.69 kg to 247.47 kg, branch carbon between 8.25 kg to 77.37 kg, leaf carbon between 1.38 kg to 15.04 kg, root carbon between 9.07 kg to 85.11 kg and total carbon between 45.39 kg to 424.99 kg.The stem carbon dioxide mitigation potential varied from 97.68 kg to 905.74 kg, branch from 30.19 kg to 283.17 kg, leaf from 5.05 kg to 55.04 kg, root from 33.19 kg to 311.50 kg and total carbon dioxide mitigation potential varied from 166.11 kg to 1555.45 kg during 2009 and 2010.